A COMPARATIVE ANALYSIS OF THE POTENTIAL OF MEDICINAL AND AROMATIC PLANTS OF SERBIA AND BULGARIA - M. Milanović, Vesna; Bucalina, Andrea (Economics of Agriculture, 2010)
Potentials of medicinal and aromatic plants can be a basis for competitive repositioning of the countries characterised by its natural raw materials or conditions for plantation growing, one of which is Serbia. Bulgaria is one of the countries which jeopardised the position of Serbia in the leading group of exporters of these plants in the region of Southeast Europe. Having that in mind, the comparative analysis of the potential of these plants aims at pointing out the advantages and disadvantages of our country in comparison with Bulgaria, and in order to improve its position on the international market. The aim of this paper is to open the options for further research of strategies for international positioning of producers and exporters of these plants and products from Serbia and a chance for cooperation with Bulgarian producers in this agricultural sector.